2017
DOI: 10.1038/bmt.2017.155
|View full text |Cite
|
Sign up to set email alerts
|

Is there any role for physical therapy in chronic GvHD?

Abstract: Chronic GvHD is the leading cause of non-relapse mortality in recipients of hematopoietic cell transplantation. Although the benefit of physical therapy (PT) has been reported in some GvHD studies, a literature gap is identified in demonstrating the exact role of different types of PT interventions and their impact on GvHD outcomes. An electronic search was undertaken using 13 peer-reviewed databases from 1994 to 2016. JADAD scoring method was used to score the quality of articles. PT interventions utilized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
4
0
2
Order By: Relevance
“…Electrotherapy modalities are widely used by rehabilitation specialists to enhance tissue healing and patients' overall recovery (Watson, 2000; Shah and Farrow, 2012). However, this literature review identified a significant gap in application and practice of electrotherapy modalities in managing a number of the common MSK manifestations related to post-HSCT, which may have otherwise been treated by electrotherapy as a standalone or as part of an exercise programme (Mohammed et al , 2018b). For example, osteonecrosis of the bones has been identified as a common complication in this patient group that results in reduced QoL and requires surgery in many cases (Atkinson et al , 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Electrotherapy modalities are widely used by rehabilitation specialists to enhance tissue healing and patients' overall recovery (Watson, 2000; Shah and Farrow, 2012). However, this literature review identified a significant gap in application and practice of electrotherapy modalities in managing a number of the common MSK manifestations related to post-HSCT, which may have otherwise been treated by electrotherapy as a standalone or as part of an exercise programme (Mohammed et al , 2018b). For example, osteonecrosis of the bones has been identified as a common complication in this patient group that results in reduced QoL and requires surgery in many cases (Atkinson et al , 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Physical rehabilitation in cGVHD can facilitate restoration of musculoskeletal system function, which would allow patients to retain some mobility and independence [6]. Once a contracture has developed active and passive ROM exercises with sustained stretch at least twice daily are necessary [7].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we and others find intensive physical therapy provides significant functional improvement. 67,68 Comprehensive local therapy offers patients with sclerodermatous lesions potential symptomatic relief.…”
Section: How Do We Choose Immunosuppressive/ Immunomodulating Agents mentioning
confidence: 99%